Glucocorticoid-associated blood glucose response and MS relapse recovery. Issue 5 (September 2017) - Goldman, Myla D.; Koenig, Scott; Engel, Casey; McCartney, Christopher R.; Sohn, Min-Woong
Abstract : Objective: To determine the relationship between MS relapse recovery and blood glucose (BG) response to IV methylprednisolone (IVMP) treatment. Methods: We retrospectively identified 36 patients with MS admitted for IVMP treatment of acute relapse who had adequate data to characterize BG response, relapse severity, and recovery. The relationship between glucocorticoid-associated nonfasting BG (NFBG) and relapse recovery was assessed. Results: Highest recorded nonfasting BG (maximum NFBG [maxNFBG]) values were significantly higher in patients with MS without relapse recovery compared with those with recovery (271 ± 68 vs 209 ± 48 mg/dL, respectively; p = 0.0045). After adjusting for relapse severity, MS patients with maxNFBG below the group median were 6 times (OR = 6.01; 95% CI, 1.08–33.40; p = 0.040) more likely to experience relapse recovery than those with maxNFBG above the group median. In a multiple regression model adjusting for age, sex, and relapse severity, a 1-mg/dL increase in the maxNFBG was associated with 4.5% decrease in the probability of recovery (OR = 0.955; 95% CI, 0.928–0.983; p = 0.002). Conclusions: These findings suggest that higher glucocorticoid-associated NFBG values in acutely relapsing patients with MS are associated with diminished probability of recovery. This relationship could reflect steroid-associated hyperglycemia and/or insulin resistance, defects in non–steroid-associated (e.g., prerelapse) glucose metabolism, or both. This study included only those admitted for an MS relapse, and it is this subset of patients for whom these findings may be most relevant. A prospective study to evaluate glucose regulation and MS relapse recovery in a broader outpatient MS population is under way.